First record of the Chilean gastropod Chiliborus in the Oligocene of Mendoza (Argentina): (Gastropoda Pulmonata: Strophocheilidae) - Miquel, Sergio Eduardo (2017)
The first record of a Chilean gastropod of the Late Oligocene of Argentina is described. The specimens show a typical general morphology and a characteristic nepionic sculpture of Chiliborus (Mollusca: Gastropoda), being the first fossil of this genus of Strophocheilidae. The locality of Quebrada Fiera (Malargüe, Mendoza Province) had provided vertebrates (a small lizard, birds and many mammals, such as notoungulates, litopterns, carnivorous marsupials), but this is the first record of an invertebrate. The mammal assemblage has been assigned to the Deseadan Mammal Age and corresponds to an open woodland environment that developed in semiarid conditions during a period of volcanic activity. The extant species of Chiliborus live in a warm oceanic climate on the west coast of Chile, in areas with vegetation that varies from sclerophyllous shrublands, small forests to transitional and mixed forests.